Short & skinny - Tatulli, Mark (Little, Brown, and Company, 2018)
Tired of being short and skinny, Mark Tatulli is determined to bulk up and hopefully end the bullying and finally talk to the girl. One summer he discovers "Star Wars" and gathers his friends to film his own version of the film. He learns that great things can come despite his size.